LOCALIZATION OF ALKALOIDS AND TANNINS FROM AERIAL PARTS OF FICUS ARNOTTIANA (MIQ.) MIQ. - Chilka, Rajeswari; Ameena, Sultana; Isnagari, Phaneendra; Sulega, Apoorva (Asian Journal of Pharmaceutical Research and Development, 2024)
The medicinally important plant Ficus arnottiana (Miq.) Miq. belongs to the family ‘Moraceae’ have been used extensively by ayurvedic practitioners in India to treat various ailments. The objective of this work was to contribute to the pharmacognostic standardization of F.arnottiana. Microscopic analysis of leaf, petiole and stem showed the presence of alkaloids, tannins, starch, protein and lipids. The leaf section shows distinct character of double layer of epidermis and a cylinder of vascular bundles in the midrib region which was not observed in the related species of F. cyclophylla and F. elliotiana. The F. cyclophylla and F. elliotiana the vascular bundles are discreet. Petiole section shows 4 to 5 distinct crescent shaped vascular bundles. Therefore, from the identified features, it proves useful for the diagnosis of the species which, together with identification of the chemical compounds and its histo-localization, provides support to their quality control.